Hiking with Nietzsche : becoming who you are - Kaag, John J., 1979- (London : Granta books, 2018)
Hiking with Nietzsche is a tale of two philosophical journeys in the Swiss Alps in Nietzsche's footsteps: one made by John Kaag as an introspective teenager, the other seventeen years later as a husband and father, with his wife and small child in tow. As he hikes, Kaag considers not only Nietzsche's ideals but how his philosophy relates to us in the 21st century. And he finds that the process of climbing and the inevitable missteps give you the chance, in Nietzsche's words, to 'become who you are'.
Keywords: Filosofie